Video data analysis : how to use 21st century video in the social sciences - Nassauer, Anne, 1982-; Legewie, Nicolas M. (London : SAGE Publications Ltd., 2022)
Provides a flexible framework for working with video data and understanding what it says about social life. With examples from a range of real video research projects, the book showcases step-by-step how to analyse any kind of data, including both found and generated videos. It also includes a non-technical discussion of computer vision and its opportunities for social science research.
Includes bibliographical references (pages 251-293) and index.
Keywords: Social sciences -- Research -- Audio-visual aids; Social sciences -- Research -- Moral and ethical aspects; Digital video